Relationship between timing of achieving energy sufficiency and clinical outcomes in critically ill patients - Xiangfeng Yue; Xiaoxi Zhu; Xiaoxi Zhu; Yongchun Li; Yongchun Li; Xuemin Huang; Quanjun Lyu (Frontiers in Nutrition, 2025)
Background and aimMalnutrition is a critical challenge in intensive care unit (ICU) patients, with the timing of energy sufficiency being a key yet debated factor in nutritional support. This study aimed to investigate the association between the timing of achieving energy sufficiency (defined as ≥70% of daily energy targets, 17.5 kcal/kg/day) in critically ill patients and their clinical outcomes, providing evidence-based guidance for ICU nutritional protocols.MethodsIn this prospective observational study, adult patients admitted to the ICU for ≥3 days were stratified into three groups based on the time to achieve energy sufficiency: early (≤3 days), middle (4–7 days), and late (>7 days). Clinical outcomes, including in-hospital mortality, 60-day mortality, ICU length of stay, and gastrointestinal complications, were compared across groups. Cox proportional hazards regression models were used to assess the independent association between energy sufficiency timing and mortality, while restricted cubic spline (RCS) analysis explored nonlinear dose–response relationships using days to energy sufficiency as a continuous variable. Statistical analyses were performed using SPSS 25.0 and R 4.2.3 (two-tailed tests, α = 0.05).ResultsA total of 826 critically ill patients were initially screened, with 584 meeting the predefined inclusion and exclusion criteria and ultimately enrolled in this study. The middle-group patients (achieving energy sufficiency at 4–7 days) demonstrated the lowest in-hospital mortality (15.6%) and 60-day mortality (28.5%), significantly lower than the late group (32.0 and 49.0%, respectively; p < 0.001). After adjusting for confounders (age, BMI, disease severity, etc.), both early and middle energy sufficiency remained independent protective factors against 60-day mortality (HR = 0.398 and 0.399, respectively; p < 0.001). RCS analysis revealed a nonlinear dose–response relationship: mortality decreased with delayed energy sufficiency up to day 6, after which mortality risk significantly increased (p < 0.001 for overall correlation; inflection point at day 6).ConclusionThe timing of achieving energy sufficiency (17.5 kcal/kg/day) is significantly associated with 60-day mortality in ICU patients. Combining RCS-derived inflection point (day 6) and intergroup comparisons, the optimal window for achieving energy sufficiency appears to be 4–6 days post-ICU admission, balancing metabolic stability and tissue repair needs while avoiding early overfeeding risks.